T Lymphocyte–Endothelial Interactions: Emerging Understanding of Trafficking and Antigen-Specific Immunity - Carman, Christopher V.; Martinelli, Roberta (Frontiers in Immunology, 2015)
Antigen-specific immunity requires regulated trafficking of T cells in and out of diverse tissues in order to orchestrate lymphocyte development, immune surveillance, responses and memory. The endothelium serves as a unique barrier, as well as a sentinel, between the blood and the tissues and as such it plays an essential locally tuned role in regulating T cell migration and information exchange. While it is well established that chemoattractants and adhesion molecules are major determinants of T cell trafficking, emerging studies have now enumerated a large number of molecular players as well as a range of discrete cellular remodeling activities (e.g. transmigratory cups and invadosome-like protrusions, IPLs) that participate in directed migration and pathfinding by T cells. In addition to providing trafficking cues, intimate cell-cell interaction between lymphocytes and endothelial cells provide instruction to T cells that influence their activation and differentiation states. Perhaps the most intriguing and underappreciated of these ‘sentinel’ roles is the ability of the endothelium to act as a non-hematopoietic ‘semi-professional’ antigen-presenting cell. Close contacts between circulating T cells and antigen-presenting endothelium may play unique non-redundant roles in shaping adaptive immune responses within the periphery. A better understanding of the mechanisms directing T cell trafficking and the antigen-presenting role of the endothelium may not only increase our knowledge of the adaptive immune response but also empower the utility of emerging immunomodulatory therapeutics.